Updating needs of librarianship professionals: diagnosis of professors and graduates of the School of Librarianship, Documentation and Information (EBDI) of the National University of Costa Rica. - Mora Valverde, María Marjorie (2008)
This project is a diagnosis of the updating and training needs of professionals in librarianship and its results will be used for the design of a Continuing Education Program in Librarianship, which will be implemented by the School of Librarianship, Documentation and Information of the National University. The study population is composed of all the teachers of the School of Libraries, Documentation and Information of the National University, in the month of October 2007, and all the graduates of bachelor's degree of the EBDI from 2000 to 2007. The results of this research were obtained by means of a questionnaire that was filled out by each one of the members of these two populations, which correspond to the 25 EBDI professors and 18 bachelor's degree graduates. It also presents the information obtained from interviews conducted with the heads of the main institutions that are characterized by hiring many professionals in librarianship.